Government with Algorithm: Strategy to Improve Synchronous Public Service Using Artificial Intelligence (AI) in Indonesia - Faizal Madya; Rulinawaty Rulinawaty; Daniel Pasaribu (Budapest International Research and Critics University, 2022)
This study reviews how government by algorithm uses AI in the public sector. Artificial intelligence has been heralded as the next source of business value in the public and private sectors. Building on organizational resource-based theory and recent work on AI in organizational contexts, this study (1) identifies AI-specific resources that together create AI capabilities, (2) develops models to capture AI capabilities in public services, and (3) looks at public trust capabilities, and (3) examines the relationship between AI capabilities and creativity and organizational performance. The research method uses a qualitative approach with a case study strategy. This type of case study is explanatory. Empirical findings show that Artificial Intelligence (AI) changes how government agencies carry out their functions and roles to improve performance, compliance, and security activities in public service and public goods. Rapid developments in AI can reduce essential governance costs and improve quality and power-based administrative data so that government performance is more efficient and effective. The implications prove that AI capabilities result in increased creativity and organizational performance.